Evaluating the Effectiveness of APM Tools (Dynatrace, AppDynamics) in Real-Time Performance Monitoring - Ramdoss, Vasudevan Senathi; Rajan, Priya Darshini Mukunthu (The Eastasouth Journal of Information System and Computer Science, 2025)
Application Performance Monitoring (APM) tools play a crucial role in ensuring optimal performance and reliability of cloud-based applications. Dynatrace and AppDynamics are two leading APM solutions that provide real-time monitoring, diagnostics, and performance optimization. This paper evaluates their effectiveness in real-time performance monitoring by analyzing their capabilities, impact on system performance, and ability to detect and resolve performance issues.